Determinants of Share Prices: An Empirical Study on the Services Sector in India - Jadhav, Jaideep Gulabrao; Badade, Kunal Shriniwas (Indian Journal of Finance, 2012)
In the last decade and half, many emerging capital markets have undergone drastic changes in terms of markets, micro-structure changes, specifically in secondary markets. The researchers focus on the various determinants of equity share prices with reference to the Indian stock market. Securities investors would be interested in knowing the determinants of pricing of equity shares, which he plans to hold for periods ranging from short to infinity. The objective is to find out the association between Earning Per Share, Dividend Per Share, Dividend Yield, Book Value Per Share and Price Earnings Ratio with the Market Price of equity shares. The final sample of this research study consists of fifteen companies selected from the service sectors like Banking, Health Care and Information Technology in India. The data used for the analysis was collected for the last five financial years. A linear multiple regression model was selected to measure the combined effects of explanatory variables on the dependent variable. The data analysis and interpretation part shows the significant relationship between independent variables and dependent variable.